Terminological Distinctions in Translation: Array - Mangher (Chitac), Ana-Maria (Journal of Danubian Studies and Research, 2020)
This paper examines some basic theoretical concepts in order to identify a few useful aspects in the translation of medical texts. The main aim of this work is to introduce different textual typologies from the perspective of some well-known linguists and translation scholars such as: Anna Trosborg, Basil Hatim, Ian Mason, Albrecht Neubert, Katharina Reiss, and to establish the way in which textual typology influences the translation of the medicaltexts which represents the subject of my doctoral research. This will be done starting from the assumption that a text type allows the translator to recognize the function and purpose of the text as well as the author’s intention. Thus, the translator will inevitably resort to different techniques and strategies in order to successfully render the source text into the target language.We will define terms such as: text, discourse, genre, text type and text typology, identifying and explaining the relationships between these concepts and their implication for translation.